Development of a rapid and efficient DNA-based method to detect and quantify adulterations in coffee (Arabica versus Robusta). (June 2018) - Combes, Marie-Christine; Joët, Thierry; Lashermes, Philippe
Abstract: Worldwide appreciated beverage, "Arabica" and "Robusta" coffee produced from Coffea arabica and C. canephora respectively, represents a high economical value product. Arabica coffee is generally sold at a higher price than Robusta coffee. As both intentional and accidental adulterations of Arabica with Robusta are frequent, a reliable, inexpensive, and high-throughput adulteration detection technology is required for the coffee industry. We developed a DNA-based authentication method that overcomes limitations of metabolic profiling of Robusta and Arabica coffees. The identification of Arabica and Robusta coffee species, as well as the quantification of their relative proportion in blends were performed by High Resolution Melting (HRM) analysis on green and roasted coffee products. For a more sensitive detection method, chloroplastic rather than nuclear genetic variations were targeted between Coffea species. By the developed method, the Coffea species of origin can be quickly differentiated and in case of adulteration, the percentage can be determined. Highlights: A cheap and convenient adulteration detection method is required in coffee sector. Chloroplastic DNA-based authentication method has been developed. Quantitative HRM is a fast, cheap and high-throughput method tool for coffee sector. Coffea species of origin can be identified in green and roasted coffee. Robusta adulteration as low as 1% in Arabica products can be detected.